On An Efficient Solution Of The Dirichlet Problem For Properly Elliptic Equation In The Elliptic Domain - Babayan, A. H.; Veziryan, R. M. (Հայաստանի ԳԱԱ)
The fourth-order properly elliptic equation with multiple root is considered in the elliptic domain. The conditions, necessary and sufficient for the unique solvability of the Dirichlet problem for this equation are found, and if these conditions fail the defect numbers of this problem are determined. The solution of the problem is found in explicit form.
Keywords: Mathematics